Biodegradation mechanism of chloramphenicol by Aeromonas media SZW3 and genome analysis. (January 2022) - Tan, Zewen; Yang, Xiuyue; Chen, Lian; Liu, Yiling; Xu, Hui-Juan; Li, Yongtao; Gong, Beini
Graphical abstract: Highlights: Aeromonas media strain SZW3 is capable of biodegrading chloramphenicol (CAP). The optimal CAP biodegradation conditions were concluded. Three novel products and possible degradation pathways were proposed. Four possible CAP biodegradation genes were identified through genome analysis. Abstract: The overuse of chloramphenicol (CAP) due to its low price is detrimental to ecological safety and human health. An earthworm gut content dwelling bacterium, Aeromonas media SZW3, was isolated with capability of CAP biodegradation, and the CAP degradation efficiency reached 55.86% at day 1 and 67.28% at day 6. CAP biodegradation kinetics and characteristic of strain SZW3 determined the factors that affect CAP biodegradation. Thirteen possible biodegradation products were identified, including three novel biodegradation products (CP1, CP2 and CP3), and three potential biodegradation pathway were proposed. Biodegradation reactions include amide bond hydrolysis, nitro group reduction, acetylation, aminoacetylation, dechlorination and oxidation. Genome analysis suggested that the coding gene of RarD (CAP resistance permease), CAP O-acetyltransferase, nitroreductase and haloalkane dehalogenase may be responsible for CAP biodegradation. The proposed complete biodegradation pathway and genome analysis by strain SZW3 provide us new insight of the transformation route and fate of CAP in the environment.